KAJIAN PENILAIAN KONDISI JEMBATAN MENGGUNAKAN PEDOMAN PEMERIKSAAN JEMBATAN 2022 DAN BRIDGE HEALTH INDEX (BHI) - Saraswati, Ayu; Aditya, Muhammad Fathur (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Indonesia remains committed to prioritizing national infrastructure development in an effort to boost regional economic growth. Proper optimization of funds is necessary, given the high maintenance costs. Thus, proper procedures and systematic implementation are essential. To achieve the best results, a bridge management system is needed. However, in its application, the bridge management system in Indonesia still faces assessment challenges (bias) that can affect the results. Therefore, several approaches are needed to complement development and provide input. To evaluate the assessment system in the 2022 Bridge Inspection Guidelines, this study aims to adopt the Bridge Health Index (BHI) method. This study attempts to identify the advantages and disadvantages of both approaches, which are expected to contribute significantly to the development of bridge management systems in Indonesia. Based on the results of the analysis, the BHI method provides a priority order for handling based on bridge condition values, while for the 2022 Guidelines, the priority order cannot yet be determined because there is still a bias between the condition values of one bridge and another, so further analysis is needed. Based on the comparison results, damage to the core elements of the bridge will be prioritized when these elements are weighted. The ranking results can be made clearer by using a numerical assessment range and a weighting scheme, which reduces bias. This perspective is important to provide input for developers and contribute to the growth of Indonesia's bridge management system in the future.